2017
DOI: 10.1590/1983-21252017v30n201rc
|View full text |Cite
|
Sign up to set email alerts
|

Relative Competitiveness of Goosegrass Biotypes and Soybean Crops

Abstract: -The goosegrass (Eleusine indica (L.) Gaertn) is an annual plant that has a low-level resistance to glyphosate (LLRG), resulting in control failure in genetically modified soybean crops for resistance to this herbicide. Alleles related to resistance may cause changes in the plant biotype, such as inferior competitive ability. Thus, the objective of this work was to evaluated the competitive ability of soybean crops and susceptible and resistant (LLRG) goosegrass biotypes. Replacement series experiments were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…This indicates less damage to the crop than to arrow-leaf sida, since the values presented by the weed were very far from the expected, presenting a concave line and a detrimental effect on stature (Figure 1). Franco et al (2017), evaluating the relative competitiveness of goose grass biotypes infesting soybean, observed that plant height presented values similar to or below the hypothetical line, indicating that the competition did not cause damage to the crop.…”
Section: /10mentioning
confidence: 93%
“…This indicates less damage to the crop than to arrow-leaf sida, since the values presented by the weed were very far from the expected, presenting a concave line and a detrimental effect on stature (Figure 1). Franco et al (2017), evaluating the relative competitiveness of goose grass biotypes infesting soybean, observed that plant height presented values similar to or below the hypothetical line, indicating that the competition did not cause damage to the crop.…”
Section: /10mentioning
confidence: 93%
“…On the other hand, crabgrass (Digitaria spp.) (C 4 ), beggarticks (C 3 ), wild poinsettia (C 3 ) and goosegrass (C 4 ) exhibited decrease in HEI, LA and SDW when competing with soybean (Agostinetto et al 2013;Forte et al 2017;Franco et al 2017). Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…A utilização de herbicidas dentro do cronograma de tratos culturais de uma lavoura é indispensável para garantir altas produtividades, e evitar a competição por recursos como água, luz e nutrientes entre a espécie cultivada e as plantas daninhas que ocupam o mesmo espaço. Essa competição interespecífica traz prejuízos mútuos aos organismos envolvidos, mais evidentes na cultura de interesse econômico, que culmina em redução de produtividade (Franco et al, 2017).…”
Section: Introductionunclassified